Frog and Toad are friends - Lobel, Arnold ([New York] : HarperCollins Publishers, 1970)
Presents five tales about the adventures of best friends Frog and Toad.
"Reading with help"--Cover.
"HarperTrophy"--Cover p. [4].
Wilson's Children, November 1996
Notable/Best Books (A.L.A.), June 1998
Book Links (A.L.A.), November 1998
Child Study Children's Book Committee, September 1996
Keywords: Friendship -- Fiction; Frogs -- Fiction; Toads -- Fiction; Friendship -- Fiction; Frogs -- Fiction; Toads -- Fiction; Readers (Elementary)